Efektivitas Penerapan Model Discovery Learning Berbantuan Geogebra - Suradi Suradi; Ahmad Zaky; Ghina Farida (Issues in Mathematics Education (IMED), 2023)
Penelitian ini bertujuan untuk mengetahui efektivitas penerapan model discovery learningberbantuan GeoGebra terhadap hasil belajar pada pembelajaran matematika siswa kelas VIII SMPdengan indikator efektivitas pembelajaran yaitu hasil belajar siswa, aktivitas siswa, dan respons siswa.Penelitian ini adalah pra-eksperimen dengan pendekatan kuantitatif desain one group pretest posttestmenggunakan teknik pengambilan sampel cluster random sampling. Populasi pada penelitian ini siswakelas VIII SMP dan sampel penelitian terdiri dari satu kelompok kelas eksperimen sebanyak 23 siswa.Data hasil belajar siswa diperoleh dengan pemberian pretest dan posttest, data aktivitas siswa diperolehdengan lembar observasi aktivitas siswa, serta data respons siswa diperoleh dengan angket responssiswa. Adapun data tersebut dianalisis dengan menggunakan statistik deskriptif dan statistik inferensialsehingga secara umum dapat disimpulan bahwa penerapan model discovery learning berbantuanGeoGebra efektif diterapkan pada pembelajaran matematika siswa kelas VIII SMP.Kata Kunci: Efektivitas, Hasil Belajar Matematika, Model Discovery Learning, GeoGebraThis study aims to determine the effectiveness of the application of the GeoGebra-assisteddiscovery learning model to learning outcomes in mathematics for grade VIII junior high school studentswith indicators of learning effectiveness, namely student learning outcomes, student activities, andstudent responses. This study is a pre-experiment with a quantitative approach to a one group pretest-posttest design using cluster random sampling techniques. The population in this study was students inclass VIII junior high school, and the research sample consisted of one experimental class group of 23students. Pretests and posttests were used to collect data on student learning outcomes; student activityobservation sheets were used to collect data on student activity; and student response questionnaireswere used to collect data on student response. The data were analyzed using descriptive statistics andinferential statistics so that, in general, it can be concluded that the application of the GeoGebra-assisteddiscovery learning model is effectively applied to mathematics learning for grade VIII junior high schoolstudents.Keywords: Effectiveness, Mathematics Learning Outcomes, Discovery Learning Model, GeoGebra